Assessment of the Environmental Impact of Gharraf River in the Shat Shatra Area of Shatra District - Khairy Alrawi, Areaj; Oudah Alomari, Abbas (International Journal of Engineering and Technology, 2018)
Iraqi water resources are exposed to pollution due to the dumping of solid and liquid waste into the river without treatment. This is the objective of research to assess the environmental, social and economic impacts of the river. To achieve this goal, the method of direct assessment was adopted. In this way, the environmental impacts are determined, their nature and their interpretation in a quantitative or qualitative manner. Three study stations were selected for the period (four month September to December 2012). The models were withdrawn from the stations twice a month and their results were compared with Iraqi water standards and determinants. Most of the findings of the research are to comply with Iraqi water determinants and to have many environmental, economic and social impacts determined by the EIA method. The most important recommendations are the fencing of river banks in urban rivers and preventing the dumping of solid and liquid waste into the river without treatment.Â